Portuguese architect's career - Baêna, Maria Teresa Melo e Abreu Sanches de (2016)
This work project addresses the differences and similarities in Portuguese architects’ careers. As a study in the Human Resources Management area, where a contemporary career concept has been gaining strength, it is focused on architects’ careers since they are artistic/technical professional workers with no boundaries or specific motivations. A total of 21 semi-structured in-depth interviews were conducted and studied, with different architects from different age groups and paths, using a qualitative methodology approach. The interviews explored themes as the reasons for deciding to be an architect, challenges and opportunities, academic paths, best projects and future prospects. This study revealed that Portuguese architects have specific motivations, relations and expertise that reflect particular reasons why, how and with whom architects work and what is to them a successful career as an architect.